2021
DOI: 10.48550/arxiv.2107.10008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Architecture-Specific Performance Optimization of Compute-Intensive FaaS Functions

Abstract: FaaS allows an application to be decomposed into functions that are executed on a FaaS platform. The FaaS platform is responsible for the resource provisioning of the functions. Recently, there is a growing trend towards the execution of compute-intensive FaaS functions that run for several seconds. However, due to the billing policies followed by commercial FaaS offerings, the execution of these functions can incur significantly higher costs. Moreover, due to the abstraction of underlying processor architectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Evaluating the general performance of FaaS platforms and improving the performance of FaaS functions has also been actively researched [8,10]. In [10], the authors present the Serverless Application Analytics Framework (SAAF), to improve observability on the performance of FaaS functions on commercial FaaS platforms.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Evaluating the general performance of FaaS platforms and improving the performance of FaaS functions has also been actively researched [8,10]. In [10], the authors present the Serverless Application Analytics Framework (SAAF), to improve observability on the performance of FaaS functions on commercial FaaS platforms.…”
Section: Related Workmentioning
confidence: 99%
“…SAAF currently supports multiple FaaS platforms and several different programming languages. In our previous work [8], we examined the underlying processor architectures on GCF and demonstrated the usage of Numba [21], a Just-in-Time (JIT) compiler based on LLVM for optimizing and improving the performance of compute-intensive Python based FaaS functions. We showed that the optimization of FaaS functions can improve performance by 18.2x and save costs by 76.8%.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…These containers are commonly referred to as function instances [22], [23] 1 https://github.com/andreas-grafberger/fedless and contain the function's language-specific runtime environment. For commercial FaaS platforms, the function instances are launched on the FaaS platforms' traditional Infrastructureas-a-Service Virtual Machines as described in [24], [25]. The runtime is responsible for relaying the invocation events, context information, and responses between the FaaS platform and the function.…”
Section: Introductionmentioning
confidence: 99%